2012
DOI: 10.1007/s00268-012-1574-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Medically Treated Hypocalcemia after Surgery for Graves’ Disease: A Swedish Multicenter Study of 1,157 Patients

Abstract: Risk factors for medically treated hypocalcemia varied at different times of follow-up. Young age, operative time, type of hospital, and parathyroid autotransplantation were associated with early postoperatively hypocalcemia. Preoperative β-blocker treatment was a risk factor at the first follow-up. At early and late follow-up, gland weight and reoperation for bleeding were associated with medically treated hypocalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
53
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 39 publications
8
53
1
3
Order By: Relevance
“…This result correlates with a large registry-based study that found younger patients have an increased incidence of hypocalcemia after thyroidectomy for GD. 13 Since definitions of hypocalcemia in these series include (in part) the development of symptoms, this was hypothesized to be due to younger patients possibly being more sensitive to and having more symptoms of hypocalcemia in the post-operative period, consistent with a previous analysis of hypocalcemia after thyroidectomy for GD. 26 However, this result is not consistent across studies, and some studies have identified older age as a risk factor for post-thyroidectomy complications.…”
Section: Discussionsupporting
confidence: 53%
“…This result correlates with a large registry-based study that found younger patients have an increased incidence of hypocalcemia after thyroidectomy for GD. 13 Since definitions of hypocalcemia in these series include (in part) the development of symptoms, this was hypothesized to be due to younger patients possibly being more sensitive to and having more symptoms of hypocalcemia in the post-operative period, consistent with a previous analysis of hypocalcemia after thyroidectomy for GD. 26 However, this result is not consistent across studies, and some studies have identified older age as a risk factor for post-thyroidectomy complications.…”
Section: Discussionsupporting
confidence: 53%
“…Issues regarding case volume and setting (university vs district general hospitals, MDT participation) are well documented across the generality of surgery, 22,38 cancer management 21,23 and endocrine practice. 19,20 These apply at both individual surgeon and hospital level with patients being more likely to receive appropriate surgical management for DTC in a higher volume centre. 39 BAETS recommends a minimum annual caseload of 25 thyroidectomies per year (personal communication from John Watkinson, Past President of BAETS, 2011) and the multidisciplinary guideline recommends 30.…”
Section: Discussionmentioning
confidence: 99%
“…Improved outcomes are associated with increased case volume in both thyroid surgery [17][18][19][20] and the wider consideration of cancer management [21][22][23] in a multidisciplinary team (MDT) setting. 5 Traditionally the realm of general surgeons, often with an endocrine interest, thyroid surgery has in the last 15 years seen a higher proportion of service delivery by ear, nose and throat (ENT)/head and neck surgeons.…”
mentioning
confidence: 99%
“…Two meta-analyses [5,7] reported lower incidence of hypocalcemia after the use of UD, whereas two other studies found no difference [6,21]. Medication for hypocalcemic symptoms was considered a reliable indicator of clinically relevant hypocalcemia in the early postoperative period, which was in line with another study [22].…”
Section: Discussionmentioning
confidence: 80%